2011
DOI: 10.1038/ki.2011.116
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic identification of vanin-1 as a marker of kidney damage in a rat model of type 1 diabetic nephropathy

Abstract: At present, the urinary albumin excretion rate is the best noninvasive predictor for diabetic nephropathy (DN) but major limitations are associated with this marker. Here, we used in vivo perfusion technology to establish disease progression markers in an animal model of DN. Rats were perfused with a reactive ester derivative of biotin at various times after streptozotocin treatment. Following homogenization of kidney tissue and affinity purification of biotinylated proteins, a label-free mass spectrometry-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 53 publications
3
41
0
2
Order By: Relevance
“…Vanin-1, an epithelial glycosylphos-phatidylinositol-anchored pantetheinase (Aurrand-Lions et al, 1996;Pitari et al, 2000), participates in the response to oxidative stress in vivo (Berruyer et al, 2004). A recent study showed that the protein levels of renal vanin-1 increased in rats with streptozotocin-induced diabetic nephropathy, and urinary vanin-1 was detected in patients with diabetic nephropathy (Fugmann et al, 2011). Therefore, it is anticipated that urinary vanin-1 is a potential biomarker for the early detection of AKI.…”
Section: N-acetyl-␤-d-glucosaminidase (Nag)mentioning
confidence: 99%
“…Vanin-1, an epithelial glycosylphos-phatidylinositol-anchored pantetheinase (Aurrand-Lions et al, 1996;Pitari et al, 2000), participates in the response to oxidative stress in vivo (Berruyer et al, 2004). A recent study showed that the protein levels of renal vanin-1 increased in rats with streptozotocin-induced diabetic nephropathy, and urinary vanin-1 was detected in patients with diabetic nephropathy (Fugmann et al, 2011). Therefore, it is anticipated that urinary vanin-1 is a potential biomarker for the early detection of AKI.…”
Section: N-acetyl-␤-d-glucosaminidase (Nag)mentioning
confidence: 99%
“…Since pantetheinase protein was originally purified from horse kidney and vanin-1/VNN-1 mRNA is abundant in kidney tissue, one can speculate that detection of pantetheinase levels in urea and/or changes in mRNA expression in kidney tissues would reflect renal tissue damage. One report by Fugmann et al (36) showed that concentrations of VNN1 distinguished diabetic patients with macroalbuminuria from those with normal albuminuria. Another report by Hosohata et al (37) showed that urinary pantetheinase is derived from damaged tubular kidney cells.…”
Section: Pantetheinase Family Genes and Proteins As Indicators Of Hummentioning
confidence: 99%
“…In the liver, the mRNA expression levels of VNN1, as well as its activity, are induced upon fasting (18,19). A clinical study showed that the concentrations of VNN1 in pooled human urine distinguished diabetic patients with macroalbuminuria from those with normal albuminuria (20). In addition, the combination of VNN1 and MMP9 has been suggested as a novel blood biomarker panel to discriminate pancreatic cancer-associated diabetes from type 2 diabetes (21).…”
mentioning
confidence: 99%